A single-center initial experience on laparoscopic pancreatic operation combined with hepatic arterial resection and reconstruction - Xu, Jie; Wang, Jia-Guo; Lei, Kai; Liu, Zuo-Jin (Frontiers in Surgery, 2023)
Objective: This study aims to summarize our single-center initial experience in laparoscopic pancreatic operation (LPO) combined with hepatic arterial resection and reconstruction, as well as to demonstrate the feasibility, safety, and key surgical procedure for LPO. Methods: We retrospectively analyzed 7 patients who had undergone LPO combined with hepatic arterial resection and reconstruction in our center from January 2021 to December 2022. The clinical data of these 7 patients were collected and analyzed. Results: In our case series, two patients underwent passive arterial resection and reconstruction due to iatrogenic arterial injury, and five patients underwent forward arterial resection and reconstruction due to arterial invasion. The arterial anastomosis was successful in 5 cases, including 2 cases of end-to-end in situ and 3 cases of arterial transposition, and the vascular reconstruction time was 38.28±15.32 min. There were two conversions to laparotomy. The postoperative recovery of all patients was uneventful, with one liver abscess (Segment 4) and no Clavien III–IV complications. We also share valuable technical feedback and experience gained from the initial practice. Conclusions: Based on the surgeon’s proficiency in open arterial resection and reconstruction and laparoscopic technique. This study demonstrated the feasibility of total laparoscopic hepatic arterial resection and reconstruction in properly selected cases of arterial involvement or iatrogenic arterial injury. Our initial experience provides valuable information for laparoscopic pancreas surgery with arterial resection and reconstruction.